The membrane-tethered transcription factor ANAC089 serves as redox-dependent suppressor of stromal ascorbate peroxidase gene expression - Klein, Peter; Seidel, Thorsten; Stöcker, Benedikt; Dietz, Karl-Josef (Frontiers in Plant Science, 2012)
The stromal ascorbate peroxidase (sAPX) functions as central element of the chloroplast antioxidant defence system. Its expression is under retrograde control of chloroplast signals including redox- and reactive oxygen species (ROS)-linked cues. The sAPX promoter of Arabidopsis thaliana was dissected in transient reporter assays using mesophyll protoplasts. The study revealed regulatory elements up to -1868 upstream of the start codon. By yeast-one-hybrid screening, the transcription factor ANAC089 was identified to bind to the promoter fragment 2, (-1262 to -1646 bp upstream of translational initiation). Upon mutation of the cis acting element CACG, binding of ANAC089 was abolished. Expression of a fused fluorescent protein version and comparison with known endomembrane markers localized ANAC089 to the trans golgi network and the ER. The transcription factor was released upon treatment with reducing agents and targeted to the nucleus. Transactivation assays using wild type and mutated versions of the promoter showed a partial suppression of reporter expression. The data indicate that ANAC089 functions in a negative retrograde loop, lowering sAPX expression if the cell encounters a highly reducing condition. This conclusion was supported by reciprocal transcript accumulation of ANAC089 and sAPX during acclimation to low, normal and high light conditions.